EVALUASI PENGENDALIAN ECENG GONDOK (EICHORNIACRASSIPES) DI DANAU TONDANO KABUPATEN MINAHASA DALAM MASA PANDEMI COVID-19 - Moningkey, Gerry Sean; Andaki, Jardie A.; Dien, Christian R.; Jusuf, Nurdin; Rarung, Lexy K.; Moningkey, Ruddy D. (Universitas Sam Ratulangi, 2021)
AbstractThis research was conducted to evaluate the factors that determine so that the control of water hyacinth in Lake Tondano since the existence of this weed in 1996 until now has not provided maximum results. The research method used is a qualitative research method, more specifically a 'Case Study' with the research object of 'place' which in this case is Lake Tondano, the 'actors' namely the government and citizens of the Minahasa district, and 'activities'. namely the cleaning of water hyacinth in Lake Tondano by the government and the community that has been going on for more than two decades. The data collection methods applied were